Nature of Bimetallic Oxide Sb2MoO6/rGO Anode for High‐Performance Potassium‐Ion Batteries. Issue 17 (18th June 2019) - Wang, Jue; Wang, Bin; Liu, Zhaomeng; Fan, Ling; Zhang, Qingfeng; Ding, Hongbo; Wang, Longlu; Yang, Hongguan; Yu, Xinzhi; Lu, Bingan
Abstract: Potassium‐ion batteries (KIBs) are one of the most appealing alternatives to lithium‐ion batteries, particularly attractive in large‐scale energy storage devices considering the more sufficient and lower cost supply of potassium resources in comparison with lithium. To achieve more competitive KIBs, it is necessary to search for anode materials with a high performance. Herein, the bimetallic oxide Sb2 MoO6, with the presence of reduced graphene oxide, is reported as a high‐performance anode material for KIBs in this study, achieving discharge capacities as high as 402 mAh g −1 at 100 mA g −1 and 381 mAh g −1 at 200 mA g −1, and reserving a capacity of 247 mAh g −1 after 100 cycles at a current density of 500 mA g −1 . Meanwhile, the potassiation/depotassiation mechanism of this material is probed in‐depth through the electrochemical characterization, operando X‐ray diffraction, transmission electron microscope, and density functional theory calculation, successfully unraveling the nature of the high‐performance anode and the functions of Sb and Mo in Sb2 MoO6 . More importantly, the phase development and bond breaking sequence of Sb2 MoO6 are successfully identified, which is meaningful for the fundamental study of metal‐oxide based electrode materials for KIBs. Abstract : Sb2 MoO6 /rGO composites are demonstrated as a high‐performance bimetallic oxide anode for potassium‐ion batteries, unraveling the nature of the anode with Sb nanoparticles generated from the destruction of Sb2 MoO6 lattice primarily contributing to the high capacity while the Mo element improves the conductivity and forms an amorphous K–Mo–O matrix to enhance the stability by providing a buffering space.